Ablation of Akt2 and AMPKα2 rescues high fat diet-induced obesity and hepatic steatosis through Parkin-mediated mitophagy - Shuyi Wang; Jun Tao; Huaguo Chen; Machender R. Kandadi; Mingming Sun; Haixia Xu; Gary D. Lopaschuk; Yan Lu; Junmeng Zheng; Hu Peng; Jun Ren (Elsevier, 2021)
Given the opposing effects of Akt and AMP-activated protein kinase (AMPK) on metabolic homeostasis, this study examined the effects of deletion of Akt2 and AMPKα2 on fat diet-induced hepatic steatosis. Akt2-Ampkα2 double knockout (DKO) mice were placed on high fat diet for 5 months. Glucose metabolism, energy homeostasis, cardiac function, lipid accumulation, and hepatic steatosis were examined. DKO mice were lean without anthropometric defects. High fat intake led to adiposity and decreased respiratory exchange ratio (RER) in wild-type (WT) mice, which were ablated in DKO but not Akt2−/− and Ampkα2−/− mice. High fat intake increased blood and hepatic triglycerides and cholesterol, promoted hepatic steatosis and injury in WT mice. These effects were eliminated in DKO but not Akt2−/− and Ampkα2−/− mice. Fat diet promoted fat accumulation, and enlarged adipocyte size, the effect was negated in DKO mice. Fat intake elevated fatty acid synthase (FAS), carbohydrate-responsive element-binding protein (CHREBP), sterol regulatory element-binding protein 1 (SREBP1), peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), peroxisome proliferator-activated receptor-α (PPARα), PPARγ, stearoyl-CoA desaturase 1 (SCD-1), phosphoenolpyruvate carboxykinase (PEPCK), glucose 6-phosphatase (G6Pase), and diglyceride O-acyltransferase 1 (DGAT1), the effect was absent in DKO but not Akt2−/− and Ampkα2−/− mice. Fat diet dampened mitophagy, promoted inflammation and phosphorylation of forkhead box protein O1 (FoxO1) and AMPKα1 (Ser485), the effects were eradicated by DKO. Deletion of Parkin effectively nullified DKO-induced metabolic benefits against high fat intake. Liver samples from obese humans displayed lowered microtubule-associated proteins 1A/1B light chain 3B (LC3B), Pink1, Parkin, as well as enhanced phosphorylation of Akt, AMPK (Ser485), and FoxO1, which were consolidated by RNA sequencing (RNAseq) and mass spectrometry analyses from rodent and human livers. These data suggest that concurrent deletion of Akt2 and AMPKα2 offers resilience to fat diet-induced obesity and hepatic steatosis, possibly through preservation of Parkin-mediated mitophagy and lipid metabolism.